Effects of single dose arginine supplementation on lactate threshold and performance - Yavuz, H. U.; Demirel, A. H.; Turnagöl, H.; Sahin, Z. (Archivos de medicina del deporte, 2008)
This study has been designed to investigate the possible effects of pre-exercise acute arginine supplementation on lactate threshold and lactate metabolism in male wrestlers. Nine volunteer male wrestlers who were wrestling in Turkish Greco-roman 1.st league participated to the study. Test- retest protocol was done on the same subjects. After 12 hours fasting (during the night) venous blood samples were taken before the exercise protocol for determining the plasma amino acid profiles and arginine levels. Incremental exercise protocol was applied and oxygene consumption was measured during the exercise, heart rate and plasma lactate levels were measured during the exercise and recovery. Exercise protocol started at 90 watts on bicycle ergometry and the load was increased 30 watts in every 3 minutes. Exercise was continued till the subjects can not go on cycling at the desired working loads or the subjects wanted to stop. Plasma amino acid profiles were also determined after the exercise protocol. Study has been conducted by using cross over design. Half of the subject took 1.5 gram /10 kg body weight L-arginine while other half were taking same amount of wheat bran before the fi rst exercise and same amount of L-arginine before the second exercise protocol. Results showed that in the same working loads there was no difference for the mean lactate levels between arginine and placebo groups (p>0.05) while there was a right shift on working load lactate graphic. There was no difference for maximum oxygen consumption (arginine 52.47±4.01, placebo 52.07±5.21) and maximum heart rates (arginine 181.09±13.57, placebo 185.89±7.38) (p>0.05). Time to exhaustion was longer with L-arginine supplementation (1386.8±69.8 sec) compare to placebo (1313±90.8 sec). Plasma arginine, ornithine and citrulline levels before and after the exercise were found higher with L-arginine supplementation. These results suggest that L-arginine supplementation can have beneficial effects on exercise performance but can not explain the metabolic pathways which are responsible from these effects.